THE ROLE OF AKIDAH AKHLAK TEACHERS AS MOTIVATORS IN DEVELOPING STUDENTS’ ISLAMIC PERSONALITIES AT MAN 1 JAMBI CITY - Ahmad Ridho; M. Thontowi (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the role of Akidah Akhlak teachers as motivators in developing students’ Islamic personalities at State Madrasah Aliyah 1 in Jambi City, with a focus on the motivational strategies teachers employ in guiding students to face the challenges of social media use in the digital age. This study employed a qualitative approach using a descriptive research design. Data were collected through observation, interviews, and documentation from one Akidah Akhlak teacher as the primary informant, as well as one school principal, one Guidance and Counseling (BK) teacher, one homeroom teacher, and four students as supporting informants, all selected purposively at State Senior High School 1, Jambi City. The research was conducted from May 18 to June 18, 2026. Data were analyzed through the stages of data reduction, data presentation, and concluding. The results of the study indicate that Akidah Akhlak teachers serve as motivators by providing advice, setting a good example, fostering Islamic behavior, offering spiritual guidance, and providing guidance on the wise use of social media. The strategies implemented included fostering the habit of greeting others, promoting study discipline, enforcing classroom rules, character development, and presenting examples of inspirational figures. These roles led to increased enthusiasm for learning, improved discipline, a more religious attitude, and better social behavior among students. This study implies that the successful development of students’ Islamic personalities requires the active role of teachers as motivators, supported by cooperation among schools, families, and the community. A limitation of this study is its scope, which was confined to a single madrasah; therefore, the findings cannot yet be generalized to all Islamic educational institutions. This study offers novelty because it specifically examines the role of Akidah Akhlak teachers as motivators in developing students’ Islamic personalities in the digital age, while considering the influence of social media on student behavior. The research findings are expected to serve as a reference for teachers, schools, and future researchers in developing Islamic character education strategies relevant to contemporary developments.